2015
DOI: 10.1163/22134808-00002479
|View full text |Cite
|
Sign up to set email alerts
|

Task-Specific, Age Related Effects in the Cross-Modal Identification and Localisation of Objects

Abstract: We investigated age-related effects in cross-modal interactions using tasks assessing spatial perception and object perception. Specifically, an audio-visual object identification task and an audio-visual object localisation task were used to assess putatively distinct perceptual functions in four age groups: children (8-11 years), adolescents (12-14 years), young and older adults. Participants were required to either identify or locate target objects. Targets were specified as unisensory (visual/auditory) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 123 publications
(152 reference statements)
2
10
0
Order By: Relevance
“…The simple meaningless visual images (ellipse with horizontal or vertical arrows) and auditory sounds (540 Hz and 560 Hz) were selected according to the study of Giard and Peronnet (1999). The semantic visual images and their corresponding sounds were selected on the basis that each animal had high naming agreement and familiarity norms for both older and younger adults (Barrett & Newell, 2015). The semantic characters (Simplified Chinese) and their corresponding flat tone speech sounds were selected according to the study by Xu et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…The simple meaningless visual images (ellipse with horizontal or vertical arrows) and auditory sounds (540 Hz and 560 Hz) were selected according to the study of Giard and Peronnet (1999). The semantic visual images and their corresponding sounds were selected on the basis that each animal had high naming agreement and familiarity norms for both older and younger adults (Barrett & Newell, 2015). The semantic characters (Simplified Chinese) and their corresponding flat tone speech sounds were selected according to the study by Xu et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…The current study also aimed to address the issue of ceiling or floor unisensory responses, which could provide an alternative explanation for enhanced MSI observed in older adults. Mahoney and colleagues (2014) noted that participants in their "No MSI" effect group did not appear to exhibit a multisensory benefit since they were already so fast to respond to one unisensory (usually tactile) stimulus (see also Barrett and Newell, 2015). The authors point out that these older adults might still be capable of MSI, however the visual stimulus was not facilitating a multisensory response.…”
mentioning
confidence: 99%
“…These age-related increases in distractibility are common, but not universal. For example, Campbell et al (2010) assessed trajectory deviations caused by introducing a visual distractor as participants made saccades towards a multisensory target, and found no effect of age, while Barrett and Newell (2015) similarly showed that a spatially incongruent distractor impaired response times in younger and older adults equally. Townsend et al (2006) further found no age-related behavioural differences in an fMRI study of modality-specific attention, though the authors do report that older adults displayed significantly increased frontoparietal activations in response to irrelevant stimuli.…”
Section: Large Conflicts -Cross-sensory Distraction and Interferencementioning
confidence: 99%